E3 Ligase Nedd4 Promotes Axon Branching by Downregulating PTEN - Drinjakovic, Jovana (Cell Press, 2010)
Regulated protein degradation via the ubiquitin-proteasome system (UPS) plays a central role in building synaptic connections, yet little is known about either which specific UPS components are involved or UPS targets in neurons. We report that inhibiting the UPS in developing Xenopus retinal ganglion cells (RGCs) with a dominant-negative ubiquitin mutant decreases terminal branching in the tectum but does not affect long-range navigation to the tectum. We identify Nedd4 as a prominently expressed E3 ligase in RGC axon growth cones and show that disrupting its function severely inhibits terminal branching. We further demonstrate that PTEN, a negative regulator of the PI3K pathway, is a key downstream target of Nedd4: not only does Nedd4 regulate PTEN levels in RGC growth cones, but also, the decrease of PTEN rescues the branching defect caused by Nedd4 inhibition. Together our data suggest that Nedd4-regulated PTEN is a key regulator of terminal arborization in vivo.